National planning and agricultural benefits in the rice sector: ruralDaule - Olivero Arias, Edison; Alvarado Mórquez, Mariana (Revista Universidad de Guayaquil, 2015)
Describe the criteria of the rice farmers in the rural area of Daule, on agricultural benefits, within the framework of public initiatives permitted by law and Ecuadorian planning, the objective of this research Information obtained through qualitative research, through a semi-structured survey probability accord ding to a sampling of opinion towards 1 00 person, was not relevant to achieve the goal. This was done by students of distance of the University of Guayaquil; who found once analyzed data in categories that 68%of respondents received some form of agricultural benefit, while the remaining 48% fails it give an opinion on these benefits. Highlights in general that it prompted even some kind of support to the Executive and agreater socialization, control and planning environment to the realization of the agricultural benefits